Fundamental of Entrepreneurship ENT300 : Crostata Varieta / Muhammad Taufiq Bolhie... [et al.] - Bolhie, Muhammad Taufiq; Morrison, Samuel; Augustine, Delicia; Suhaimin, Nurul Syazlyn (2018)
A business plan is a written document detailed on execution plan of the business proposed by entrepreneurs. The business plan include the details of the company. the flow of the administration. human resource plan" strategies of marketing plan" also the flow of the financial planning. "Crostata Varieta" prepares this business planning for this several purpose.